Inclusive Justice and The Future Human Rights and Criminal Law in The Era of Globalization (Lembaga Contrarius Indonesia, 2026)
This study examines the application of the principle of inclusive justice in criminal law enforcement in Indonesia, grounded in human rights values. In the context of a national legal system still dominated by a retributive approach, inclusive justice offers a new, more humane and participatory paradigm. This approach emphasizes the importance of protecting vulnerable groups and encourages the use of restorative mechanisms such as diversion and termination of prosecution based on restorative justice. Using normative legal research methods with conceptual and analytical approaches, this study demonstrates that integrating human rights values into criminal law can strengthen legal legitimacy, increase the efficiency of the justice system, and foster social reconciliation. This study recommends transforming legal culture and increasing the capacity of law enforcement officials as strategic steps towards a more just and civilized legal system.